Effects of age, replicative lifespan and growth rate of human nucleus pulposus cells on selecting age range for cell-based biological therapies for degenerative disc diseases. (3rd July 2016) - Lee, JS; Lee, SM; Jeong, SW; Sung, YG; Lee, JH; Kim, KW
Abstract : Autologous disc cell implantation, growth factors and gene therapy appear to be promising therapies for disc regeneration. Unfortunately, the replicative lifespan and growth kinetics of human nucleus pulposus (NP) cells related to host age are unclear. We investigated the potential relations among age, replicative lifespan and growth rate of NP cells, and determined the age range that is suitable for cell-based biological therapies for degenerative disc diseases. We used NP tissues classified by decade into five age groups: 30s, 40s, 50s, 60s and 70s. The mean cumulative population doubling level (PDL) and population doubling rate (PDR) of NP cells were assessed by decade. We also investigated correlations between cumulative PDL and age, and between PDR and age. The mean cumulative PDL and PDR decreased significantly in patients in their 60s. The mean cumulative PDL and PDR in the younger groups (30s, 40s and 50s) were significantly higher than those in the older groups (60s and 70s). There also were significant negative correlations between cumulative PDL and age, and between PDR and age. We found that the replicative lifespan and growth rate of human NP cells decreased with age. The replicative potential of NP cells decreased significantly in patients 60 years old and older. Young individuals less than 60 years old may be suitable candidates for NP cell-based biological therapies for treating degenerative disc diseases.